Structural Health Monitoring from Sensing to Processing - Abdel Wahab, Magd; Lai Zhou, Yun; Manuel Mendes Maia, Nuno (IntechOpen, 2018)
Structural health monitoring (SHM) has attracted more attention during the last few decades in many engineering fields with the main aim of avoiding structural disastrous events. This aim is achieved by using advanced sensing techniques and further data processing. SHM has experienced booming advancements during recent years due to the developments in sensing techniques. The reliable operation of current, sophisticated, man-made structures drives the development of incipient reliable damage diagnosis and assessment. This book aims to illustrate the background and applications of SHM from both sensing and processing approaches. Its main objective is to summarize the advantages and disadvantages of SHM methodologies and their applications, which may provide a new perspective in understanding SHM for readers from diverse engineering fields.